Spatiotemporal Evolution Mechanism and Spatial Correlation Network Effect of Resilience in Different Shrinking Cities in China - Weijun Yu; Siyu Zhang; Entao Pang; Huihui Wang; Yunsong Yang; Yuhao Zhong; Tian Jing; Hongguang Zou (Land)
Bolstering the resilience of shrinking cities (SCs) is essential for maintaining urban dynamic security and fostering sustainable development. Accurately assessing and revealing the resilience level and impact mechanism of SCs to cope with disturbances and shocks has become a hot topic of research in urban sustainable development. In this research, we presented a systematic conceptualization of the fundamental components of urban shrinkage (US) and urban resilience (UR) and, based on US and UR theories, constructed a methodological framework aimed at investigating the spatiotemporal evolution mechanism and spatial correlation network effect of resilience in different SCs in China. This paper initially evaluates the UR levels of various types of SCs in China by establishing an evaluation model for US and a multidimensional evaluation index system for UR based on the theoretical frameworks, aligned with the national context in China. We also define the spatiotemporal evolution patterns of UR for different types of SCs. Subsequently, this paper employs a coupled coordination model and a geographical detector model to elucidate the influencing mechanisms on UR of different types of SCs, focusing on UR subsystems and indicators. Finally, this paper empirically examines the spatial correlation network effects of UR under various US scenarios using a social network analysis model. The results show that many SCs have progressively adjusted to the challenges posed by US, and the UR of SCs has shown an upward trend from 2010 to 2021. Cities with higher US levels generally show lower coordination in UR subsystems. The comprehensive utilization rate of industrial solid waste and road freight per capita are crucial for improving the UR of cities with higher US levels. Moreover, US probably strengthens UR connections between cities, facilitating resilience transmission and dissemination. These findings advance UR research within the US framework and offer theoretical foundations and planning guidance for environmentally friendly and high-quality development in shrinking cities.